2017
DOI: 10.3928/01477447-20161213-03
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ultrasound-Guided Intra-articular Hip Injections Performed in the Orthopedic Clinic

Abstract: Intra-articular hip injections have proven clinical value for both diagnostic and therapeutic purposes. Historically, these injections have been performed by radiologists using fluoroscopic guidance. This necessitates a radiology referral, delays the injection, and represents lost productivity for the orthopedist. Ultrasound-guided intra-articular hip injections have been described in the radiology literature with excellent accuracy. These injections were performed by radiologists. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…As Otjen et al 12 noted in their study of US-guided joint injections for MR arthrography in pediatric patients, US is likely more technically challenging than fluoroscopy, requiring more dexterity because concomitant transducer and needle manipulation is needed. In our practice, we have experienced an expeditious learning curve for USguided hip injections, which is similar to that reported by Byrd et al 4 and Balog et al 2 While our data do not demonstrate a clearly defined significant decrease in filling defects over time, no instances of inappropriately placed contrast were reported in the final 10 months of the data collection period. In the hands of an experienced clinician, the US method is safe, reliable, and reproducible.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As Otjen et al 12 noted in their study of US-guided joint injections for MR arthrography in pediatric patients, US is likely more technically challenging than fluoroscopy, requiring more dexterity because concomitant transducer and needle manipulation is needed. In our practice, we have experienced an expeditious learning curve for USguided hip injections, which is similar to that reported by Byrd et al 4 and Balog et al 2 While our data do not demonstrate a clearly defined significant decrease in filling defects over time, no instances of inappropriately placed contrast were reported in the final 10 months of the data collection period. In the hands of an experienced clinician, the US method is safe, reliable, and reproducible.…”
Section: Discussionsupporting
confidence: 87%
“…Byrd et al 4 reported on a large series of 206 hip injections performed by a nurse practitioner, achieving a 98% accuracy rate. More recently, Balog et al 2 reported a 96% accuracy rate for a series of 48 US-guided hip injections performed in an orthopaedic clinic by orthopaedic surgeons and orthopaedic physician assistants. Upon review of the data, the sole limiting variable to a successful MR arthrogram was inappropriately placed contrast, which led to a decreased volume of contrast within the hip capsule on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 94.4% of institutions reported using image guidance, with 50% using ultrasound and 44.4% fluoroscopy. Ultrasound guidance has been shown in adult patients to be safe and accurate for intra-articular placement 26 and has found growing utilization for the evaluation of the painful pediatric hip. 5 , 11 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…By using palpation of anatomic landmarks, these injections can achieve a high level of accuracy, be convenient and be cost-effective, allowing physicians to perform diagnostic and therapeutic injections in the clinic rather than referring the patient to a radiologist [ 4 ]. Intra-articular hip injections are typically performed using ultrasound or fluoroscopic guidance [ 5–8 ]. Ultrasound-guided hip injections may be performed in the orthopaedic clinic [ 5 ], though these injections are more commonly performed under fluoroscopy guidance by a radiologist, with confirmation provided by the intra-articular positioning of radiopaque contrast material [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-articular hip injections are typically performed using ultrasound or fluoroscopic guidance [ 5–8 ]. Ultrasound-guided hip injections may be performed in the orthopaedic clinic [ 5 ], though these injections are more commonly performed under fluoroscopy guidance by a radiologist, with confirmation provided by the intra-articular positioning of radiopaque contrast material [ 6 ]. Recently, however, non-image-guided techniques have been described for the hip using anatomic landmarks and palpation [ 9–12 ].…”
Section: Introductionmentioning
confidence: 99%